Effect of Substitution of Pb for Mg on the Photovoltaic Properties of Methyl‐Ammonium Lead Iodide Perovskites. Issue 3 (19th January 2022) - Tablero Crespo, César
Abstract: To know if Pb can be substituted by less toxic Mg without reducing the photovoltaic efficiency of the methyl‐ammonium lead iodide perovskites, the microscopic contributions to the absorption coefficients and efficiencies are analyzed as a function of the gradual substitution of Pb by Mg. The absorption coefficients are obtained from first principles and used later to obtain efficiencies. To identify and quantify the most important contributions to the photovoltaic properties as a function of cell thickness, both the absorption coefficients and efficiencies are split as an exact many‐species expansion. From these results, the substitution of Pb by Mn would lead to solar cells with similar photovoltaics characteristics, except if the solar cells are ultra‐thin. Abstract : The methyl‐ammonium lead iodide perovskite, an absorber material for achieving low‐cost high‐efficiency photovoltaics, contains the toxic element lead. An attractive strategy is to replace Pb with Mg. In this work, this possibility is analyzed by carrying out a splitting of the most important contributions to the absorption coefficients and efficiencies.